Perception of representativeness of the Assembly of Huila 2020-2023 - García Peñaloza, John Edisson; Antury Bermúdez, Liliana Marcela; Almario Calderón, Yuly Margarita (Multidisciplinar (Montevideo), 2024)
In this article we present the perception that huilenses have about the Assembly of Huila period 2020-2023; the investigative work process was developed with citizens of the department of Huila, linking stakeholders from different sectors who have the opportunity to comment on the management, characteristics that define the assembly, aspects to improve, visible deputy, criteria that they take into account when voting for an aspiring candidate for that important Corporation that represents the region, exercising political control over the management of the departmental administration and decentralized entities, analyzing, debating and approving the ordinances among other constitutional and legal functions. In the objective search for information, we also took into account the concept of the twelve deputies from Huila, who, by completing a self-assessment survey (Google Form), answered questions related to the management and fulfillment of functions, among other variables that provide us with real data to be confronted with the feelings of the citizens, who are ultimately responsible for electing the members of this political-administrative organ